PEMBELAJARAN BAHASA INDONESIA SECARA ONLINE PADA MASA PANDEMI COVID-19 DI SMA ISLAM TERPADU NUR HIDAYAH SUKOHARJO - Nusantari, Septirini Sekar; Sumarwati, Sumarwati; Anindyarini, Atikah (Universitas Sebelas Maret, 2020)
This study aims to determine the obstacles to learning Indonesian online and efforts to solve them at SMAIT Nur Hidayah Sukoharjo. This type of research is descriptive qualitative. The data collection technique was carried out by document analysis, observation and interviews. Data analysis used in this research is data collection, data reduction, data presentation and conclusion. The results showed that the obstacles experienced by teachers and students during online learning were supervision, learning applications, learning facilities and internet networks.